2015
DOI: 10.1159/000442749
|View full text |Cite
|
Sign up to set email alerts
|

Serum Biomarkers of Allergic Contact Dermatitis: A Pilot Study

Abstract: Background: Allergic contact dermatitis (ACD) is an inflammatory skin disease caused by repeated skin exposure to contact allergens. The goal of this pilot study was to identify inflammatory proteins which can serve as biomarkers for ACD. Methods: We measured levels of 102 cytokines, chemokines, and growth factors in the sera of 16 ACD patients during acute and remission phases, and 16 healthy volunteers. Results: Serumlevels of adiponectin, chemokine (C-C motif) ligand 5 (CCL5), C-reactive protein (CRP), chit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…Nevertheless, the mechanisms of the association between RBP-4 and these diseases are still unclear. It remains similar with the other allergic conditions [12,17].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Nevertheless, the mechanisms of the association between RBP-4 and these diseases are still unclear. It remains similar with the other allergic conditions [12,17].…”
Section: Discussionsupporting
confidence: 81%
“…In a case-control study of prepubertal children, high plasma RBP-4 levels correlated with lower forced expiratory volume in 1 second/forced vital capacity (FEV1/FVC) or forced expiratory flow at 25% and 75% (FEF25-75) in male asthmatics; however, no significant difference in its level was found between asthmatics and controls [12]. Zinkeviciene et al [17] suggested RBP-4 as a possible serum biomarker in allergic contact dermatitis. However, to our knowledge, none has examined their association in general populations.…”
Section: Discussionmentioning
confidence: 99%
“…Platelet factor 4 (PF4) and β-thromboglobulin (β-TG) are the most abundantly expressed CXC chemokines in platelet α-granules that could be released in high concentrations following activated platelets [48]. Significant differences in plasma levels of PF4 or β-TG were found between many inflammatory skin diseases and normal controls, such as systemic sclerosis [49], allergic contact dermatitis [50], and atopic dermatitis [51], elevated expression indicating the critical role of platelet activation. β-TG together with PF4 levels in psoriasis was also reported to be higher than in healthy controls, and PF4 levels were correlated with PASI [51].…”
Section: In the Role Of Psoriasis Inflammationmentioning
confidence: 99%
“…[7] Increased hsCRP is found in many skin diseases including allergic contact dermatitis, mycosis fungoides, hidradenitis suppurativa, and psoriasis. [89101112] Increased CRP in psoriatic patients was correlated with active arthritis, psoriasis area severity index (PASI) score, and with an increased incidence of cardiovascular diseases. [13] Patients with increased hsCRP levels were found to have a better response to cyclosporine therapy.…”
Section: Introductionmentioning
confidence: 99%